The Impact of Foreign Direct Investment: the case of Kazakhstan's Oil Industry - Yestayev, Baurzhan (2007)
Given the rapid influence of economic liberalisation and market globalization, foreign direct investment plays a leading role in today's economic landscape. Foreign direct investment in Kazakhstan has rapidly increased in the last decade, and has become an important subject matter of the Kazakhstan economy. The oil industry has a biggest share in revenue among all other industries in the country. This research will examine the impact that inward foreign direct investment in Kazakhstan's oil industry has on the patterns of growth and development in the country. It can be concluded that FDI has a positive impact on the country; however, due to the country's drawbacks, these contributions of FDI to Kazakhstan's economy are still limited.